REPRSENTASI PEREMPUAN DALAM IKLAN TELEVISI (Studi Analisis Semiotika Iklan Beng Beng Versi “Great Date”) - Radita Gora (Universitas Bunda Mulia, 2016)
Television advertisement is still considered as audio-visual communication media that conveys the message with high effectiveness value resulting feed back to society. Therefore, television advertising should pay attention to aspects of advertising messages delivered to the audience. From the text of advertising version ‘Great Date’, there is a tendency for women’s position. Based on the results of research using Roland Barthes semiotics, it was found that the use of signifier and signified by seeing denotation and connotation meaning represent the nature of materialistic woman related to such items (guy's dream, flowers, romantic music, cool car and brown). Besides that, the portrayal of women in Beng-beng advertising is built as an object of marginalization deal with material view.Keywords: Advertising, representation, Semiotics